2020
DOI: 10.3390/ani10030498
|View full text |Cite
|
Sign up to set email alerts
|

The German Shorthair Pointer Dog Breed (Canis lupus familiaris): Genomic Inbreeding and Variability

Abstract: Simple Summary: In order to protect domestic animals' biodiversity, a deep knowledge of the genomic makeup is required. The authors describe the genomic architecture of the German Short Hair Pointer breed and analyze the inbreeding levels under a genomic and a genealogic perspective. Twenty-four dogs from Italy were genotyped and analyzed jointly with 10 dogs from USA, whose genotypes were available from a published research. The authors investigated the genomic structural variation of the breed using runs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Pedigree analyses based on extensive data revealed average litter size and life expectancy for the Leonberger dogs included in our study that are in agreement with previously reported results [ 52 ]. Long ROH segments (~ 10 Mb) occur as a result of recent inbreeding, whereas short ROH (< 2 Mb) indicate genomic regions that are identical by descent from older ancestors [ 12 ]. In the Leonberger dogs studied here, the 1- to 2-Mb segments account for approximately 25% of the detected ROH and those that are longer than 8 Mb account for about 20% (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pedigree analyses based on extensive data revealed average litter size and life expectancy for the Leonberger dogs included in our study that are in agreement with previously reported results [ 52 ]. Long ROH segments (~ 10 Mb) occur as a result of recent inbreeding, whereas short ROH (< 2 Mb) indicate genomic regions that are identical by descent from older ancestors [ 12 ]. In the Leonberger dogs studied here, the 1- to 2-Mb segments account for approximately 25% of the detected ROH and those that are longer than 8 Mb account for about 20% (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphic microsatellite marker genotype data have been used to evaluate the genetic diversity in dogs (e.g. [7,8]), and more recently, genomewide single nucleotide polymorphism (SNP) genotype data have been used in several breeds [9][10][11][12][13]. Based on SNP data, runs of homozygosity (ROH) can be characterized, which enable quantification of the extent of inbreeding in diploid individuals, especially in the case of incomplete, unreliable, or missing pedigree information [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these is the epha6 gene which was found to be associated with temperament in Guzerat (Bos indicus), a Brazilian breed of domestic cattle [63]. The second one of these is the fmn1 gen which appears to be associated with energy and trainability in dogs (Canis familiaris) [64]. Another one was the dyrk1ab gene, where knockout studies in zebrafish found it to be associated with traits related to social deficiencies relevant to autism [65].…”
Section: Discussionmentioning
confidence: 99%
“…Leroy et al [ 12 ] included the SHP (F = 0.035) and the Griffon Korthals (F = 0.056) in a genetic diversity study of 60 French dog populations. Italian SHPs had an F of 0.023 [ 23 ]. Because classical inbreeding coefficients do not take into account the degree of inbreeding in ancestors, ancestral inbreeding coefficients were developed some time ago [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%